The War of the Worlds - Wells, H.G (Orion Books Ltd, 2004)
H.G. Wells's hugely influential book tracks the exploits of a writer who struggles to survive an alien invasion of Victorian England. After seeing the monstrous Martians firsthand, the narrator attempts to evade their destructive mechanized vehicles and must stay on the run to avoid detection. As he meets other desperate humans, he becomes increasingly pessimistic about any chance of survival.
Keywords: Fiction; Science Fiction